2021
DOI: 10.1021/acs.langmuir.1c00314
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolinium N-Heterocyclic Carbene Ligands for Enhanced Stability on Gold Surfaces

Abstract: N-heterocyclic carbenes (NHCs) have emerged as versatile and robust ligands for noble metal surface modifications due to their ability to form compact, self-assembled monolayers. Despite a growing body of research, previous NHC surface modification schemes have employed just two structural motifs: the benzimidazolium NHC and the imidazolium NHC. However, different NHC moieties, including saturated NHCs, are often more effective in homogenous catalysis chemistry than these aforementioned motifs and may impart n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…The set of bands between 1250 and 1450 cm –1 are due to a complex coupling of the isopropyl side group hydrogens to heterocycle hydrogens, where the resulting normal modes are affected by the orientation of side groups with respect to the surface (i.e., pointing upwards or downwards) . Specifically, our spectra exhibit these bands at 1291, 1325, and 1401 cm –1 , which corresponds well with previously reported SERS spectra. , There is one consistent difference between the previously reported spectra and the signatures reported here: rather than the 1325 cm –1 band being much stronger than the 1291 cm –1 band, our spectra of imidazole on AuNPs show these bands as relatively equal in intensity (Figure a). This change may be due to a difference in the binding of ligands to the substrate surface between roughened solid Au and AuNPs, which could affect the average configuration of isopropyl side groups …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The set of bands between 1250 and 1450 cm –1 are due to a complex coupling of the isopropyl side group hydrogens to heterocycle hydrogens, where the resulting normal modes are affected by the orientation of side groups with respect to the surface (i.e., pointing upwards or downwards) . Specifically, our spectra exhibit these bands at 1291, 1325, and 1401 cm –1 , which corresponds well with previously reported SERS spectra. , There is one consistent difference between the previously reported spectra and the signatures reported here: rather than the 1325 cm –1 band being much stronger than the 1291 cm –1 band, our spectra of imidazole on AuNPs show these bands as relatively equal in intensity (Figure a). This change may be due to a difference in the binding of ligands to the substrate surface between roughened solid Au and AuNPs, which could affect the average configuration of isopropyl side groups …”
Section: Resultssupporting
confidence: 90%
“…XPS is a standard approach for investigating the chemical states of ligands on metal surfaces. In particular, the appearance of a N 1s peak between 399 and 401 eVs is used to indicate the presence of chemisorbed NHCs. ,, The characteristic N 1s XPS peak for imidazole NHC-AuNPs (Figure a) remains unchanged during the 21 day observation period for NPs suspended in both water and PBS buffer (Figures S9 and b, respectively), providing further evidence that the NHC ligand is unchanged on the nanoparticle surface in this media. No nitrogen signal was observed when citrate-capped AuNPs were exposed to PBS buffer (Figure a).…”
Section: Resultsmentioning
confidence: 89%
“…Future developments should be focused on the mechanistic investigation of electronic surface activation by NHCs via precise surface characterization and computational studies to prove the suggested activation mode of AuNMCats. Further, the structural and electronic diversification of employed carbene ligands (e. g. benzimdazol‐/imidazoline‐2‐ylidenes [81] and acyclic diamino carbenes [82] ) should grant increased tunability for target‐made catalysts with increased selectivity. In these terms, NHC@AuNC are ideal model systems to benchmark different carbene ligands and establish important structure‐to‐property relations towards NHC@AuNPs.…”
Section: Discussionmentioning
confidence: 99%
“…N-heterocyclic carbene (NHC) ligands’ strong metal-carbon bonds and highly tunable structures enable numerous applications, including organometallic catalysis, electronics, supramolecular chemistry, metal–organic frameworks, and medicinal chemistry . To add to this considerable collection, NHCs were recently shown to form robust self-assembled monolayers (SAMs) stable under electrochemical cycling, high temperatures, catalytic cycling, , and exposure to rigorous chemical environments, signifying that they are an attractive alternative to the widely used, but labile, thiols in noble-metal surface functionalization . The longevity of implantable electrochemical sensors, for example, is currently limited by the instability of thiol-SAMs …”
mentioning
confidence: 99%